Secreted Portion of Glycoprotein G of Herpes Simplex Virus Type 2 Is a Novel Antigen for Type-Discriminating Serology - Görander, Staffan (American Society for Microbiology, 2003)
The secreted portion of glycoprotein G (sgG-2) of herpes simplex virus type 2 (HSV-2) was evaluated as a novel antigen in an enzyme-linked immunosorbent assay (ELISA) format for detection of type-specific immunoglobulin G (IgG) antibodies in HSV-2-infected patients. The results were compared with those obtained by a commercially available assay, the HerpeSelect 2 ELISA (the FOCUS2 assay). Five different panels of sera were analyzed: panel A consisted of 109 serum samples from patients with a culture-proven HSV-1 infection that were Western blotting (WB) negative for HSV-2; panel B consisted of 106 serum samples from patients with a culture-proven recurrent HSV-2 infection that were WB positive for HSV-2; panel C consisted of 100 serum samples with no detectable IgG antibodies against HSV-1 and HSV-2; panel D consisted of 70 HSV-2 negative “tricky” serum samples containing antinuclear IgG antibodies or IgM antibodies against other viruses or bacteria; and panel E consisted of consecutive serum samples from 21 patients presenting with a first episode of HSV-2-induced lesions. When sera in panels A to C were analyzed, the sgG-2 ELISA and the FOCUS2 assay both showed sensitivities and specificities of ≥98%. In total, among the samples in panel D, 13 serum samples (19%) were false positive by the FOCUS2 assay and 1 serum sample (1.4%) was false positive by the sgG-2 ELISA. When the sera in panel E were analyzed, the sgG-2 ELISA detected seroconversion somewhat later than WB or the FOCUS2 assay did. We conclude that sgG-2 induces an HSV-2 type-specific antibody response and can be used for type-discriminating serology.